Expert System For Diagnosing Eczema At The Pulau Panggung Community Health Centre Using The Forward Chaining Method - Astrina, Febri Jihan; Siswanto , Siswanto; Sartika , Devi (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Eczema mostly appears when children are aged 5-12 years old, but it is also common in toddlers and adults. The main symptom of eczema is unbearable itching. Various factors contribute to eczema, including genetic factors related to skin pigmentation abnormalities, immunological disorders, and environmental factors, and prompt treatment or follow-up is necessary. This study aims to develop an expert system that can assist in diagnosing eczema using the forward chaining method at the Pulau Panggung Health Centre. Based on the results of the tests conducted, it can be concluded that the expert system for diagnosing eczema at the Pulau Panggung Health Centre can assist in determining health status and facilitate the diagnosis of eczema, thereby simplifying the expert system's process of solving problems with large amounts of data using the forward chaining method. Additionally, the expert system for diagnosing eczema at the Pulau Panggung Health Centre can be accessed via the link https://eksim-puskesmaspulaupanggung.online/. From the testing conducted, the diagnosis of eczema was based on the symptoms experienced, corresponding to the highest probability level.